The Relationship of Knowledge and Maternal Mother's Attitude in Selecting Birth Supporters at UPTD Health Benai - Zalni, Rummy Islami; Marsela, Ririn (Journal of Global Research in Public Health, 2018)
Labor is a natural process that will take place by itself, but delivery to humans at any time is threatened by complications that can harm the mother and her fetus, requiring proper supervision, rescue and services. The purpose of this study was to determine the relationship of knowledge and attitude of maternal mother in choosing birth attendant at UPTD Health Benai Year 2014. The design in this research is analytical descriptive with cross sectional study design. Sampling technique in this research using quota sampling technique that is as much as 60 maternal mother. Data analysis used was univariate (central tendency) and bivariate (chi square test). The result showed that there was significant correlation between knowledge (p-value=0,001) and attitudes (p-value = 0,000) of respondents with the selection of maternity maternity assistant in UPTD Health Benai Kuantan Singingi Regency. The implication of this research is expected the respondents more active role in exploring the knowledge about the selection of good labor force of birth so that mother and child mortality